P40 Decompensated cirrhosis discharge bundle: improving care of decompensated cirrhosis at university hospitals Sussex East. (20th September 2022) - Tizzard, James; Boza, Kubra; Austin, Mark
Abstract : Background and Aims: The increasing prevalence of chronic liver disease in the UK is an on-going challenge for the NHS as mortality, emergency hospitalisations and rates of readmissions are high in decompensated cirrhosis (DC). The British Society of Gastroenterology/British Association for the Study of the Liver (BSG-BASL) Decompensated Cirrhosis Discharge Bundle (DB) is not currently in use at University Hospitals Sussex East (UHSE) sites. The aim of this study was to assess readmission rates of patients presenting with DC over a 2-year period, to retrospectively assess the completion percentage of the BSG-BASL-DB for this patient group and to investigate if there is a correlation between these outcomes. Method: We carried out a retrospective cohort study on patients presenting to UHSE sites with DC over the period January 2018 to December 2019. The primary outcome was days to readmission from discharge. Discharge letters were reviewed to retrospectively assess the completion of the BSG-BASL-DB. Simple linear regression analysis was performed to determine if the completion percentage of BSG-BASL-DB significantly predicted days from discharge to readmission. Results: A total of 94 patients were admitted with DC to UHSE sites during the period studied. There were 154 readmissions from this group of patients in the year following discharge. Demographics: age=52.0 (±11.6) years; sex=female 35.1% (n=33/94); mean Child-Pugh Score (CPS)=9.2 (±2.2). The mean number of days to readmission from discharge was 89.5days (±94.3days). Percentage readmission within 30days and 90days of discharge was 23.4% and 38.3% respectively. The mean retrospective completion of the BSG-BASL DB was 29.9% (±5.5%). Simple linear regression analysis revealed a significant correlation between percentage completion of the discharge bundle and days to readmission from discharge (R=[0.30], R2=[0.09], beta=[5.10], p=[0.02]). The interpretation of this analysis was that 9% of the variation in days to readmission could be explained by the completion percentage of the discharge bundle. Furthermore, for each additional percentage point completion of the discharge bundle, the average number of days to readmission is expected to increase by 5.1. No correlation was found from similar analysis of age or CPS in predicting days from discharge to readmission (CPS=R2=[0.01], p=[0.66]; Age=R2=[0.02], p=[0.35]). Conclusion: The BSG-BASL-DB allows opportunistic review of care of patients with DC and implementation of evidenced-based management. Our analysis shows that greater percentage completion of the BSG-BASL-DB correlates with a longer duration to readmission for patients with DC. We hope to formally introduce the BSG-BASL-DB at UHSE sites and re-audit the data following implementation.